Enabling high-performance all-solid-state hybrid-ion batteries with a PEO-based electrolyte. Issue 48 (25th May 2022) - Yu, Meng-Xuan; Gu, Zhen-Yi; Guo, Jin-Zhi; Wang, Chun-Gang; Wu, Xing-Long
Abstract : For the first time, we have devised an all-solid-state hybrid Li/Na-ion battery, which offers a new and profound way to develop high-safety and low-cost hybrid batteries. Abstract : All-solid-state hybrid-ion batteries exhibiting a synergistic Na + /Li + de/intercalation mechanism were designed and assembled, by using modified PEO-based solid polymer electrolyte, Na2 V2 (PO4 )2 O2 F cathode, and Li metal anode. The batteries exhibited a high average working voltage of 3.88 V, and an energy density of 432.37 W h kg −1, providing a new avenue for the development of high-safety and low-cost secondary batteries.